Another point of view on side effects of antifungal compounds used in veterinary medicine - Carmen Lidia Chitescu,; Anca Nicolau (Medicamentul Veterinar, 2011)
The release of pharmaceuticals into environment has become an increasing concern in recent years. Fungi are part of the microbial flora of many animals, humans and foodstuffs, and some species can cause disease. An antimycotic or antifungal product is one that is used in the treatment of fungal infections. Even at low concentrations, antifungals exert an action against micro-organisms and exhibit selective toxicity towards them. The use of antimicrobials selects for resistant populations of micro-organisms. Development of resistance to antifungals is an increasing problem in veterinary and human medicine.